Triacylglycerol accumulation and secretion in hepatocyte cultures. Effects of insulin, albumin and Triton WR 1339. - Emmison, N (1992)
We have investigated the possibility that the apparent inhibition of very-low-density lipoprotein (VLDL)-triacylglycerol secretion by the addition of insulin to rat hepatocyte cultures may result from insulin-mediated enhancement of hepatic lipase secretion and, consequently, of extracellular triacylglycerol hydrolysis. We have, therefore, studied the effects of the inhibitor of lipase activity, Triton WR 1339, on the secretion of triacylglycerol by cultured rat hepatocytes. Incubation of hepatocyte cultures with increasing concentrations of Triton WR 1339 increased the accumulation of acylglycerol in the medium, suggesting that, in normal incubations, a substantial rate of degradation of secreted triacylglycerol does occur and that it results in an under-estimation of the rate of triacylglycerol secretion. However, Triton did not counteract the inhibitory effects of insulin, suggesting that the observed increased activity of hepatic lipase induced by the hormone cannot account for the inhibition of acylglycerol accumulation in the medium that occurred in the presence of insulin. BSA increased the accumulation of triacylglycerol in culture media by about 2-fold and also decreased the activity of hepatic lipase by 80%. A causative relationship between these two effects was supported by the further observation that Triton abolished the effects of BSA on triacylglycerol accumulation in the medium. The implications of these data for the validity of the use of Triton for the study of hepatic rates of triacylglycerol production in vivo and of secretion by hepatocytes in vitro are discussed.